ANALYSIS OF SME DEVELOPMENT STRATEGIES ON PURCHASING DECISIONS CASE STUDY UD TANJUNG JAYA SITUBONDO - Latif, Fathol; Sri D, Lusi Endang; Dassucik (Yayasan Amanah Nur Aman, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an important part of a nation's economy, including in Situbondo. Development strategies are instruments used by the government, the business world, or local authorities to achieve long-term goals through preparation and assistance to develop and improve business capabilities. Empowering MSMEs is essentially a shared responsibility between the government, society, and companies. Research findings obtained through interviews, observations, and documentation of consumers at UD Tanjung Jaya indicate a strong correlation between MSME development strategies and consumer purchasing decisions. This finding reflects that the success of a micro business is not only determined by the existence of the product itself but also by strategic approaches in business management. One of the most notable findings is that product quality is the dominant factor in purchasing decisions. It can be concluded that the interpretation of the findings indicates that SME development strategies should focus on improving product quality, price efficiency, and customer service. However, for long-term growth, there needs to be a transformation in terms of promotion, legality, and distribution expansion so that products can reach broader and more competitive market segments sustainably.